A Fé documentada: perspectivas metodológicas de organização da informação fotográfica sobre romarias de Juazeiro do Norte – Ceará - Elliott, Ariluci Goes [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
This research is justified by the need to analyze the role of the photographic image in the context of pilgrimages, since this form of communication has become a prime source for the study, scientific, cultural, political and social thought in the history of pilgrims Cariri Ceará. Aims to propose a methodology for organizing information focused on the record of the iconic photographs of the Laboratory for Information Science and Memory (LACIM). The theoretical and methodological frameworks of research lead us to: 1) map the photographs in the collection of existing pilgrims LACIM; 2) using the assumptions of Document Analysis to enable the validation of information existing in the images and obtained in the interviews; 3) develop a roadmap for identification data of the photographs; 4) identify the looks and the word of photographers using discourse analysis. The theoretical and methodological axis leaned on Document Analysis who cares about the construction, organization, dissemination and retrieval of pictures. Another procedure that was adopted was the interview with the photographers and the behavior of these professionals when faced with images in relation to click and seizure of a faith that moves. We show that information science through the transdisciplinary approach contributes its theoretical and practical framework for information in the area of communication in pursuit of knowledge contextualized by validating the capture of information processes with records and intentions of photographs. Given the proposed analysis of the photographs, we found that each procedure is punctuated documentary representation from the context of production data generated by the processes of analysis, synthesis, condensation, representation and retrieval of information content. Understand the various social, cultural, political and historical roles constructed through images, provides notice forms like photography conveys an Pilgrimage in defense...

A presente pesquisa justifica-se pela necessidade de analisarmos o papel da imagem fotográfica no contexto das romarias, uma vez que essa forma de comunicação tornou-se uma fonte privilegiada para o estudo do pensamento social, científico, cultural, político e histórico de romeiros na Região do Cariri Cearense. Objetiva propor uma metodologia de organização da informação voltada para o registro icônico das fotografias do Laboratório de Ciência da Informação e Memória (LACIM). Os enquadramentos teóricos e metodológicos da pesquisa nos levam a: 1) mapear as fotografias de romeiros existentes no acervo do LACIM; 2) utilizar os pressupostos da Análise Documental para possibilitar a validação das informações, existentes nas imagens e obtidas nas entrevistas; 3) elaborar um roteiro para identificação dos dados das fotografias; 4) identificar os olhares e a palavra dos fotógrafos utilizando a Análise de Discurso. O eixo teórico metodológico se apoiou na Análise Documental que se preocupa com a construção, organização, disseminação e recuperação das fotografias. Outro procedimento que se adotou foi a entrevista com os fotógrafos e o comportamento desses profissionais frente às imagens, em relação ao clique e apreensão de uma fé que se move. Mostramos que a Ciência da Informação através da abordagem transdisciplinar, contribui com a sua estrutura teórica e prática para a informação na área da Comunicação em busca do conhecimento contextualizado, validando a captação dos processos informacionais com os registros e intenções das fotografias. Diante da proposta de análise das fotografias, verificamos que cada procedimento de representação documental é pontuado a partir do contexto de produção de dados gerados pelos processos de análise, síntese, condensação, representação e recuperação do conteúdo informacional. Compreender os vários papéis sociais, culturais, políticos e...
Keywords: Fotografia; Análise documentária; Religião; Festas religiosas - Juazeiro do Norte (CE); Photography